Mesomegaloprepidae, a remarkable new damselfly family (Odonata: Zygoptera) from mid-Cretaceous Burmese amber. (May 2017) - Huang, Diying; Azar, Dany; Cai, Chenyang; Maksoud, Sibelle; Nel, André; Bechly, Günter
Abstract: Mesomegaloprepus magnificus gen. et sp. nov. (Odonata: Zygoptera) is described from more than 14 specimens in eight pieces of mid-Cretaceous (earliest Cenomanian, ca. 99 Ma) amber from Myanmar. Possible phylogenetic affinities with the Neotropical Latibasaliidae, Thaumatoneuridae, and Pseudostigmatinae are discussed, and a relationship with Pseudostigmatinae considered as possible, but because of conflicting evidence separate family status as Mesomegaloprepidae fam. nov. is tentatively preferred. The remarkable degree of homoplastic conflict in the wing venational similarities indicates that these represent relatively weak evidence for phylogenetic relationships. The palaeoecology, including sexual dimorphism in wing colouration, of the new taxon is discussed, and the large number of inclusions explained with possible breeding behaviour in association with water-filled tree holes (phytotelmata) of the amber tree, similar to extant Pseudostigmatinae. The position of all alleged fossil Thaumatoneuridae are discussed and revised: Eothaumatoneura ptychoptera Pongracz, 1935 from the Eocene Geiseltal locality is restored in Thaumatoneuridae. Cretaceous Euarchistigma and Paleogene Eodysagrion are tentatively retained as subfamilies Euarchistigmatinae and Eodysagrioninae in Thaumatoneuridae. Paleogene Dysagrioninae and Petrolestinae are removed from Thaumatoneuridae and attributed to a restored family Dysagrionidae, and Paleocene Latibasaliidae is transferred from Amphipterygoidea to Epallagoidea.